Detection of Common Deletion Mutations (– α3.7 and – α4.2 kb) in HBA gene and Genotype-Phenotype Correlation - Basu, Satarupa; Gupta, Soma; Baul, Shuvra Neel; De, Rajib; Sen, Aditi; Dasgupta, Shreyasi; Biswas, Arindam (Archives of Clinical and Biomedical Research, 2025)
Background: Microcytic hypochromic anemia is the most common feature of alpha-thalassemia and depends on the number of alpha genes deleted. Therefore, in this study, we aim to determine the most common deletion mutations among microcytic anemia cases of West Bengal and correlate them with different biochemical parameters and endophenotypes. Materials and methods: Two hundred and sixty patients with microcytic anemia were recruited. The GAP-PCR technique was adopted to identify the 3.7 kb and 4.2 kb deletion mutation in the HBA gene. Results: Forty patients had either 3.7 kb or 4.2 kb deletion mutations, representing ~15.38% of the microcytic anemia patient population. A statistically significant lowering of MCH values (P = 0.02) and elevated levels of Total Bilirubin (P = 0.0001), direct bilirubin (P = 0.0004), unconjugated bilirubin (P = 0.0001), SGPT (P = 0.005), SGOT (P = 0.005), ALP (P = 0.008), RBC count (P = 0.01) and Hemoglobin level (P = 0.02) were observed among the alpha-thalassemia mutation carriers than non-mutant. The study failed to show any correlation between mutation status, disease severity, and gender bias. Conclusion: The two common deletion mutations (-3.7 kb or -4.2 kb) in the HBA gene are most commonly found in microcytic anemia cases of West Bengal and can be correlated with several biochemical parameters.